Student Reflections on Implemented Chemistry Education Curriculum: An Exploration of Relevancy - Parajuli, Dilu Ram; Subedi, Rishi Ram (Tribhuvan University Journal, 2023)
This article has been carried out to identify the reflection of M. Ed. completion students toward the chemistry education curriculum. The main objective of this study is to explore reflection and relevancy of the M.Ed. chemistry curriculum. Hence, it is focused on knowing M.Ed. pass students' reflections and responses to the chemistry education curriculum, exploring its relevancy, and collecting the key insights. It carried out in a mixed (quantitative and qualitative) parallel design. Seventy students (n=70) as sample for quantitative and seven students are chosen as participants for qualitative data from different batches (2014 -2020). For this inquiry; Likert’s scale statement and open ended questionnaire are used as data collection tools. Specially, the Likert’s scale is used to collect quantitative data and similarly, qualitative data by open ended questionnaire. The quantitative data were analyzed by SPSS 25 software based on the mean value and percentage. Similarly, qualitative data were analyzed by transcription, comparing, identifying themes, coding, and their elaboration and discussion process. And, its result was summarized in five main topics based on themes (curriculum content, organization, of content, pedagogical techniques and practices, evaluation techniques and practices etc.). To include all the ideas into the same pat, the chemistry education curriculum is the foundation of the chemistry/science teacher or teaching-related job, it has a huge ground of scope and it is very important to uplift the social, economic, and intellectual status of the nation hence we have to keep changing it the time relatively.